Political Party Governance as an Institutional Challenge to the Democratic Regression in Indonesia - Prianto, Andi Luhur (Universitas Pancasakti, 2024)
The trend of democratic regression in Indonesia has been explored by many political scholars. Institutional problems are considered to be the underlying issue in the regression of political democratization that was actually built on high optimism. This research identifies and analyses Indonesia's political party governance models: oligarchy-based, centralized, corporate-based, and personalized. A qualitative literature study analyzed data to understand each model's characteristics, impacts and challenges. The research results show that oligarchy-based party governance tends to result in conflicts of interest, political stagnation and unequal political opportunities. Centralization makes coordination easier but has the potential to cause internal conflict. Meanwhile, the corporate model can reduce corrupt practices and improve the quality of policies. However, personalization-based governance often results in undemocratic decisions and internal conflict. As a suggestion, research suggests the need for internal reform in political parties to increase transparency, active participation of party members, and accountability. In this way, it is hoped that political parties can better represent society's interests and strengthen democracy in Indonesia.